2011
DOI: 10.2478/s11535-011-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and biotechnological applications of the genus Burkholderia

Abstract: Bacteria belonging to the genus Burkholderia are well known for their adaptability to habitats as diverse as freshwater sediments, lungs of cystic fibrosis patients and plant tissues. This genus includes also plant, animal and human pathogenic species, such as Burkholderia glumae, Burkholderia pseudomallei and the Burkholderia cepacia complex. Over the past few years, several newly discovered non-pathogenic plant associated Burkholderia species have raised particular interest for their potential use in plant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…This genus is known for its adaptability to diverse habitats such as freshwater sediments and plant, animal, and human tissues. It is also used to promote plant growth, the biocontrol of plant pathogens, phytoremediation, and xenobiotic degradation (Paganin et al, 2011).…”
Section: Sequencing the Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…This genus is known for its adaptability to diverse habitats such as freshwater sediments and plant, animal, and human tissues. It is also used to promote plant growth, the biocontrol of plant pathogens, phytoremediation, and xenobiotic degradation (Paganin et al, 2011).…”
Section: Sequencing the Bacterial Strainsmentioning
confidence: 99%
“…Este género es conocido por su adaptabilidad a diversos hábitats tales como sedimentos de agua fresca, tejidos de plantas, animales y seres humanos. También se usa para promover el crecimiento de plantas, biocontrol de patógenos de plantas, fitorremediación y degradación xenobióti-ca (Paganin et al, 2011).…”
Section: Sequencing the Bacterial Strainsunclassified
“…It has been classified into seventeen phenotypically similar but genotypically distinct species referring to the Burkholderia cepacia complex (Bcc) (Vandamme and Dawyndt 2011). Some species of Bcc are human opportunistic pathogens, especially in cystic fibrosis patients (Agodi et al 2001;Mahenthiralingam et al 2008;Holden et al 2009;Drevinek and Mahenthiralingam 2010;Paganin et al 2011). Some species of Bcc are human opportunistic pathogens, especially in cystic fibrosis patients (Agodi et al 2001;Mahenthiralingam et al 2008;Holden et al 2009;Drevinek and Mahenthiralingam 2010;Paganin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1940s, Bcc bacteria were first isolated by Burkholder and were identified as the causative agents of onion bulb rot (Burkholder 1950). However, it has shown that many Bcc strains possess various biological functions, such as plant growth promotion (Bevivino et al 2000;Chiarini et al 2006;Vandamme et al 2007;Paganin et al 2011;Weilharter et al 2011;Li et al 2013;Sopheareth et al 2013), bioremediation (Mohanty and Mukherji 2008) and disease resistance (Cuong et al 2011;Elshafie et al 2012). However, it has shown that many Bcc strains possess various biological functions, such as plant growth promotion (Bevivino et al 2000;Chiarini et al 2006;Vandamme et al 2007;Paganin et al 2011;Weilharter et al 2011;Li et al 2013;Sopheareth et al 2013), bioremediation (Mohanty and Mukherji 2008) and disease resistance (Cuong et al 2011;Elshafie et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation